23 mJ high-power fiber CPA system using electro-optically controlled divided-pulse amplification - Stark, Henning; Buldt, Joachim; Mueller, Michael; Klenke, Arno; Tuennermann, Andreas; Limpert, Jens (Optics Letters, 2019)
The pulse-energy scaling technique electro-optically controlled divided-pulse amplification is implemented in a high-power ultrafast fiber laser system based on coherent beam combination. A fiber-integrated front end and a multipass-cell-based back end allow for a small footprint and a modular implementation. Bursts of eight pulses are amplified parallel in up to 12 ytterbium-doped large-pitch fiber amplifiers. Subsequent spatiotemporal coherent combination of the 96 total amplified pulse replicas to a single pulse results in a pulse energy of 23 mJ at an average power of 674 W, compressible to a pulse duration of 235 fs. To the best of our knowledge, this is the highest pulse energy ever accomplished with a fiber chirped-pulse amplification (CPA) system.
CRIS-Team Scopus Importer:2023-04-20